Ubiquitin-like protein-mediated sulfur trafficking facilitates hyperthermophile dispersal in sulfur-limited environments - Peng Zhou; Xue-Qing He; Qi-Liang Lai; Yue-Hong Wu (mBio)
ABSTRACT While hyperthermophilic archaea thriving in hydrothermal vent ecosystems have been extensively studied for their remarkable adaptations to geochemical extremes, the molecular underpinnings of their dispersal strategies remain enigmatic. Central to this challenge lies their capacity to survive in environments with limited elemental sulfur (S0). The recent study by Hidese et al. (mBio 15:e00534-24, 2024, https://doi.org/10.1128/mbio.00534-24) provides critical mechanistic insights by elucidating the functional roles of three ubiquitin-like proteins (Ubls) as sulfur carriers in Thermococcus kodakarensis. These Ubls facilitate metabolic flexibility in sulfur utilization, and the Ubl-involved sulfur relay system represents an elegant adaptive solution for persistence in S0-limited niches. By enabling efficient sulfur mobilization from cysteine stores, the organism achieves metabolic homeostasis under S0 deprivation, such as biosynthesis of essential biomolecules. These findings not only reveal a previously unrecognized adaptive paradigm in sulfur utilization among hyperthermophilic archaea but also underscore the importance of metabolic plasticity for microbial dispersal and evolution.